Assessing the validity of self-report of psychopathy short-form (SRP-SF) in incarcerated offenders from Chile and Uruguay. (March 2023) - Trajtenberg, Nicolás; de Ribera, Olga Sánchez; Nivette, Amy; León-Mayer, Elizabeth; Neumann, Craig S.
Abstract: Psychopathy remains a relatively unexplored concept in Latin America. The abbreviated Self-Report Psychopathy Scale (SRP-SF) seems promising in this under-resourced context. However, the SRP-SF should be tested for measurement invariance to achieve meaningful comparison across countries in Latin America. Therefore the aims of this study were to examine the underlying factor structure of the SRP-SF in incarcerated adult male offenders from Uruguay ( n  = 331) and Chile ( n  = 208), to examine the measurement invariance of the SRP-SF across countries, and to assess the utility of SRP-SF to classify first time offenders from offenders with criminal history. Findings showed a good fit for the four-factor model in Uruguay, and both Chile and Uruguay showed invariance. Conversely, the Interpersonal and Affective factors were not associated with criminal history in the Uruguayan sample. Therefore, more studies are needed before using the SRP-SF as screening tool to classify first-time offenders and reoffenders in different countries in Latin America.